Sharps injuries among nurses and midwives in sub-Saharan Africa. (2nd January 2019) - Zhu, Shijun; Liu, Wen; Amoroso, Anthony; Blanshan, Sue; Guberski, Thomasine; Iwu, Emilia; Kiama, Beatrice; Lipscomb, Jane; Maimbolwa, Margaret; Maro, Peter; Mwakyus, Sekela; Omoni, Grace; et al.
Abstract : Background: The prevalence of blood-borne pathogens, including HIV and hepatitis B and C, remains high in sub-Saharan Africa. Nurses and midwives are therefore at high risk for occupational transmission. Aims: To examine the prevalence of sharps injuries and other work-related risks among nurses and midwives. Methods: Nurses and midwives ( n =712) in sub-Saharan Africa completed an anonymous questionnaire. Generalised estimating questions were used to analyse the data. Findings: Nurses and midwives who made home visits, engaged in direct care, were called in to work 'off-hours', and performed needle-related tasks ≥15 times/day were more likely to have sharps injuries (all P <0.05). Among those injured, only 64.2% reported their injuries appropriately. Among those who reported, only 61.5% were tested for HIV or hepatitis B and C, and only 28.2% received HIV post-exposure prophylaxis. Conclusions: Future efforts should focus on optimising work schedules, reducing unnecessary needle-related tasks, introducing safety engineered needles and improving post-exposure prophylaxis.